A generic seismic risk protocol for energy production sites - Iason Grigoratos; Ryan Schultz; Janneke van Ginkel; Thanushika Gunatilake; Stefan Wiemer; Jorien L.N. van der Wal; Annemarie G. Muntendam-Bos (Bulletin of Earthquake Engineering, 2025)
Activities related to energy production have been linked with felt (and in some cases damaging) earthquakes. Notable examples include hydraulic fracturing, wastewater disposal, geothermal systems, coal mining, carbon storage and hydropower dams. As the demand for energy continues to grow, new frontiers in energy exploration will emerge - some with the potential for induced seismicity. Thus, there is a clear need for a source-agnostic seismic risk protocol that can be applied to any activity or region. This study outlines one such implementation that uses scenario earthquakes to produce a priori risk thresholds that can be referenced against current seismicity levels on an ongoing basis. Our framework is designed to inform regulatory decisions by considering the consequences of earthquake scenarios on the population and the built environment, together with simplified forecasts of the next largest magnitude. The proposed framework can tackle both the screening process needed for permitting purposes and serve as a risk management plan during operations.